Comparing cancer and cardiovascular disease trends in 20 middle- or high-income countries 2000–19: A pointer to national trajectories towards achieving Sustainable Development goal target 3.4. (November 2021) - Bray, Freddie; Laversanne, Mathieu; Cao, Bochen; Varghese, Cherian; Mikkelsen, Bente; Weiderpass, Elisabete; Soerjomataram, Isabelle
Highlights: Among HICs, uniform declines in premature death from CVD and cancer were observed. Cancer mortality exceeded CVD in 9 of 10 HICs in 2000 and in all 10 by 2019. CVD mortality exceeded cancer in all MICs in 2000, and in 8 countries by 2019. Less than half of the studied countries are predicted to meet the SDG 3.4 target. Evidence-based, prioritized, costed and financed programmes are needed to accelerate progress. Abstract: With the 2030 Sustainable Development Goals (SDG) target of a one-third reduction in noncommunicable diseases (NCDs) less than a decade away, it is timely to assess national progress in reducing premature deaths from the two leading causes of mortality worldwide. We examine trends in the probability of dying ages 30–70 from cardiovascular disease (CVD) and cancer 2000–19 in 10 middle-income (MICs) and 10 high-income (HICs) countries with high quality data. We then predict whether the SDG target will be met in each country for CVD, cancer and for the four main NCDs combined. Downward trends were more evident in HICs relative to the MICs, and for CVD relative to cancer. CVD and cancer declines ranged from 30–60% and 20–30% in HICs over the 20-year period, but progress was less uniform among the MICs. Premature deaths from cancer exceeded CVD in nine of the 10 HICs by 2000 and in all 10 by 2019; in contrast, CVD mortality exceeded cancer in all 10 MICs in 2000 and remained the leading cause in eight countries by 2019. Two of the 10 MICs (Colombia and Kazakhstan) and seven of the HICs (Australia, Chile, Italy, New Zealand, Norway, Slovakia, and the U.K.) are predicted to meet the SDG NCDs target. Whether countries are on course to meet the target by 2030 reflects changing risk factor profiles and the extent to which effective preventative and medical care interventions have been implemented. In addition, lessons can be learned given people living with NCDs are more susceptible to severe COVID-19 illness and death.